Head and neck fascia and compartments: No space for spaces. Issue 7 (29th January 2014) - Guidera, Alice K.; Dawes, Patrick J. D.; Fong, Amy; Stringer, Mark D.; Eisele, David W.
Abstract An accurate understanding of the arrangement of cervical fascia and its associated compartments is essential for differential diagnosis, predicting the spread of disease, and surgical management. The purpose of this detailed review is to summarize the anatomic, clinical, and radiological literature to determine what is known about the arrangement of cervical fascia and to highlight controversies and consensus. The current terminology used to describe cervical fascia and compartments is replete with confusing synonyms and inconsistencies, creating important interdisciplinary differences in understanding. The term "spaces" is inappropriate. A modified nomenclature underpinned by evidence‐based anatomic and radiologic findings is proposed. This should not only enhance our understanding of cervical anatomy but also facilitate clearer interdisciplinary communication. © 2014 Wiley Periodicals, Inc. Head Neck 36: 1058–1068, 2014